Eficiência energética: soluções de melhorias energéticas para o Campus UFERSA - Pau dos Ferros - Aquino, Luíz Felipe de Souza (Universidade Federal Rural do Semi-Árido, 2017)
Energy efficiency is increasingly assuming an increasing dimension, motivated by cost reduction, by uncertainties of energy availability or by environmental issues, in any way, quality for motivation, to promote an energy efficiency in using knowledge in an applied way, employing concepts Engineering, economics and administration to energy systems. The present work focused on the study and development of practices aimed at the efficient use of electric energy at the Federal Rural Semi-Arid University (UFERSA), located in the city of Pau dos Ferros / RN, aiming at the reduction of dispersals related to consumption Electric power. For this, research was conducted on questionnaires distributed among students, teachers, technicians, administrative and outsourced. Analyzes were also performed in the energy accounts, from April 2013 to April 2017, obtaining data as contracted demand (kW), as well as their costs (R$). Finally, it was possible to identify the profile of the people with respect to the use of electric energy, as well as the energy expenditures for contracted and measured energy, allowing to contribute with efficiency solutions for a better use of electric energy without campus.
Keywords: Eficiência energética; Energia elétrica; Consumo energético; Contas de energia; Redução de energia; energy efficiency; electricity; power consumption; energy bills; reduction of energy; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA